Determinants that affect inflation rate in Malaysia: money supply, interest rate, exchange rate and oil price (Crude) / Siti Raidah Azmee and Norsafrinah Ab Ghani - Azmee, Siti Raidah; Ab Ghani, Norsafrinah (Faculty of Business and Management, 2018)
Inflation has always been continues issues over the time in Malaysia. The objective of this study is to identify the significant relationship between macroeconomic variables and inflation rate in Malaysia. This study is conducted to determine the relationship between independent variables which are money supply, interest rate, exchange rate and oil price (crude) towards inflation rate in Malaysia. The monthly time series data were obtained from Thomson Reuters DataStream and this study covers the period between October 2009 until May 2018. The tools or technique that have been used and applied to estimate the relationship between dependent variable and independent variables is Multiple Linear Regression Model. Overall findings based on Multiple Linear regression, the result concludes that money supply has statistically significant impact towards inflation rate in Malaysia with negative correlation. Meanwhile, interest rate also has a significant relationship towards inflation rate in Malaysia with a positive correlation. However, exchange rate and oil price (crude) were found to be insignificant relationship towards inflation rate in Malaysia. Theoretically, exchange rate would bring positive impact towards inflation rate, but this paper provides different results where these independent variables have negative correlation with inflation rate. Based on the results, recommendations are made for policymakers and industry to help them in mapping out suitable policies that will help them in the future.